2006
DOI: 10.4028/www.scientific.net/kem.309-311.73
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Serum Albumin Adsorption on Hydroxyapatite and Biphasic Calcium Phosphate and the Correlation with Zeta Potentials and Wettability

Abstract: Studying on the interaction between proteins and calcium phosphate implants is one of the basic subjects in biomaterials science and engineering. In this work, zeta potentials and contact angles of hydroxyapatite (HA) and biphasic calcium phosphate (BCP) ceramics were measured, and the adsorption behaviors of bovine serum albumin (BSA) on the surfaces were investigated. The adsorption isotherms of BSA on both ceramics follow the Langmuir type, however, BCP shows higher BSA adsorption ability. The differences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Therefore, HA particles always have a lower microporosity than BCP particles. Previous reports have shown that the adsorption isotherms for BSA on HA and BCP particles were of the Langmuir type [33][34][35]. In the present study, according to Figs.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Therefore, HA particles always have a lower microporosity than BCP particles. Previous reports have shown that the adsorption isotherms for BSA on HA and BCP particles were of the Langmuir type [33][34][35]. In the present study, according to Figs.…”
Section: Discussionsupporting
confidence: 62%
“…It is known that protein adsorption on a solid surface is a quite complex process, and one of the main driving forces is electrostatic interaction between the material and the protein [1,4]. Both HA and BCP have negative surface f potentials in PBS, pH 7.4 [35], and the isoelectric points (IEP) of collagen, fibrinogen and insulin are $4.5 [36], 5.8 [37] and 5.3 [38], respectively. In PBS all of the three model proteins have negative surface net charges, resulting in electrostatic repulsion between the CaP powders and the proteins.…”
Section: Discussionmentioning
confidence: 99%
“…BSA and LSZ were selected as the model proteins for their distinctly different electrostatic properties. BSA is a flexible globular macromolecule (Mw ~66 kDa) with an isoelectric point of 4.7 [ 41 ]. BSA adsorption is generally driven by its conformational change and the electrostatic interaction of surface-molecule [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…BSA is a flexible globular macromolecule (Mw ~66 kDa) with an isoelectric point of 4.7 [ 41 ]. BSA adsorption is generally driven by its conformational change and the electrostatic interaction of surface-molecule [ 41 ]. For undoped OCP, compared to the untreated samples, the preponderant BSA adsorption on the heat-treated samples could be mainly due to the lower electrostatic repulsions of surface-BSA and the conformation changes of BSA molecules on the surface based on the result of specific surface area normalization (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins act as contact for cell attachment, therefore their adsorption on implant material is important for bonding the biomaterial to the bony tissue [4]. The most abundant protein in the circulatory system is bovine serum albumin (BSA); therefore, this protein is mostly used in vitro studies in order to evaluate the bioactivity of calcium phosphate ceramic powders [4,[5][6][7] and disks [6]. In most of these studies pure or modified HAp is used.…”
Section: Introductionmentioning
confidence: 99%